Implementasi Program Wanita Agen Pancasila Melalui Pelatihan Pembuatan Cake Gula Merah Bersama Ibu-Ibu PKK Di Desa Samirejo - Wahzudik, Niam; Ningtias, Liana Anggi Dwi; Faririn, Silmika; Salsabila, Nadia (Jurnal Bina Desa, 2025)
This community service activity aims to empower women in Samirejo Village as Pancasila agent women through training in making brown sugar cake. By utilizing the local potential of brown sugar, this training is expected to increase the added value of the product, empower the community's economy, and strengthen the values of Pancasila and implement it into various aspects of daily life. The object used in this activity is brown sugar as a local superior product of Samirejo Village into brown sugar cake. The method used is socialization and training based on theory and practice by actively involving PKK mothers. The service results obtained from this activity are increasing the skills and knowledge of PKK women in processing brown sugar into high-value products. In addition, this training also succeeded in strengthening the understanding and application of Pancasila values in everyday life. This service concludes that empowering women through productive economic activities can be one of the strategies to reduce the gender gap and improve the quality of life of the community.